Penerapan Metode FMEA Dalam Meminimalkan Produk Reject Under Bracket HK2SO Di PT XYZ - Oktaviani, Revina; Putri, Devina; Suastiyanti, Dwita (Teknik Industri Universitas Ma Chung, 2025)
Competition in the manufacturing industry requires companies to produce high-quality products with a low reject rate. PT XYZ faces a high level of rejects in the Under Bracket HK2SO component, resulting in increased production costs and decreased efficiency. This study aims to identify the main causes of product defects and determine improvement priorities using the Failure Mode and Effect Analysis (FMEA) method. Data were collected over a 14-week period through process observation, operator interviews, and quality report analysis. The results show that three dominant defect types—dent, underfill, and trimming—contribute to the majority of rejects, with dent having the highest Risk Priority Number (RPN) of 320. These failure modes are influenced by improper handling procedures, suboptimal equipment conditions, and unstable product positioning on the jig. Based on the FMEA analysis, corrective actions were proposed, including installing soft-pads on trays, adding locator pins to jigs, controlling billet temperature, calibrating hammer pressure, and providing operator training. Implementation of these improvements is projected to reduce RPN values by 30–50% and decrease overall reject rates by 30–45% within 1–3 months. These findings contribute to strengthening quality control in forging processes and may serve as a reference for similar industries. Future studies are recommended to integrate FMEA with statistical methods such as Statistical Process Control (SPC) or risk-weighting techniques like AHP to enhance evaluation accuracy and the sustainability of quality improvements.